Types of Speech Act in the Galgil T-Shirt Discourse - Noviana, Nur Rakhmi; Haryadi, Haryadi; Yuniawan, Tommi (Universitas Negeri Semarang, 2020)
The purpose of this research was to analyze the types of speech acts contained in the Galgil T-shirts discourse. The research used theoretical approach, specifically pragmatic and methodological approach which belong to descriptive qualitative. The data in this research were fragments of speech in the Galgil T-shirts discourse. The data were collected by listening technique then continued to simak bebas libat cakap technique and note taking techniques. The heuristic method was used to analyze data. The Data had been analyzed then being presented informally. The results of this research was speech acts in this discourse varies greatly. The types of speech acts contained in the Galgil T-shirt discourse were locutionary, illocutionary, perlocutionary, direct, indirect, literal, non- literal, and direct literal.